Možnosti snížení radikality operací v axile a značení axilárních lymfatických uzlin v rámci terapie karcinomu prsu - Dostálek, L; Šašková, P (Klinicka onkologie, 2017)
BACKGROUND: Axillary dissection (AD) is an integral part of the surgical staging of breast cancer. This operation can be source of major long term complications, e. g., lymphedema. Reducing the radicality of these operations has been the subject of many clinical trials, especially those addressing the metastatic infiltration of axillary lymph nodes uncovered either by clinical staging or by sentinel lymph node (SLN) biopsy (when the clinical staging was negative). Exact clinical (mainly ultrasonographic) staging and marking of the lymph nodes detected by staging plays a key role in deciding the optimum clinical regimen. PURPOSE: Three possibilities were tested in clinical trials: The possibility of replacing the AD by radiotherapy in the case of tumorous infiltration of SLN, when clinical staging was negative; the possibility of omitting AD (in patients with positive clinical axillary staging) and replacing it with SLN biopsy after neoadjuvant chemotherapy; and the possibility of marking lymph nodes in axilla that were suspected of infiltration at the time of clinical staging. RESULTS: The studies showed clear evidence that avoiding AD was safe in oncology patients who showed infiltration of axillary SLN and negative clinical staging. Despite the high false negativity of using SLN biopsies in patients with a positive clinical staging after neoadjuvant chemotherapy, this false negativity could be reduced by using lymph node marking. By implementing these methods, it should be possible to define exactly the group of patients in whom complete pathological remission occurs after neoadjuvant chemotherapy.Key words: breast neoplasms - axilla - lymph nodes The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 17. 4. 2017Accepted: 2. 7. 2017.
Keywords: klinické zkoušky jako téma; lymfadenektomie; Lymphatic Metastasis; axila; Clinical Trials as Topic; nádory prsu; lymfatické metastázy; Neoplasm Staging; staging nádorů; ženské pohlaví; Breast Neoplasms; Lymph Node Excision; Humans; biopsie sentinelové lymfatické uzliny; Female; Axilla; Sentinel Lymph Node Biopsy; lidé